European Railway Review / Celebrating over 20 Years of Working Together in Rail - Waters Craig (European Railway Review, 2016)
Improving Rolling Stock for the Future, Safety it's my Priority, Two New Tracks for Belgium's Busiest Railway Line, ProRail... on the Right Track!, HZ Infrastruktura Leading the Biggest EU Project in Croatia, Rail Financing Challenges.